Vzdolžna in sočasna napoved učnih dosežkov pri prvošolcih - Zupančič, Maja (Šolsko polje, 2007)
A study was performed to investigate the role of personality, non-verbal cognitive ability, home environment and attendance of pre-school as contemporaneous and longitudinal predictors of academic achievement in first graders. A sample of children attending preschools from age 1 to 3 was followed-up over the pre-school years. When they started primary schooling the sample was extended by a group of children not attending pre-school prior to school entry. The children's personality characteristics at ages 3, 4, 5 and 6 were rated by mothers, fathers and teachers. Except at age 3, the children's non-verbal ability was assessed and the parents provided self-report on their parental practices when the children were 3 and 6 years old. At the end of the first grade teachers evaluated children's attainment ofperformance standards in Slovene, Mathematics, and Environmental Education. Results from stepwise regression analyses revealed that the attainment of performance standards in the three school subjects was contemporaneously and longitudinally best predicted by children's non-verbal ability and conscientiousness-openness as perceived by the teachers. Parenting practices, parental education and pre-school attendance did not add significantly to the prediction of performance standards, over and above the contribution of child ability and teacher-rated child personality.
Keywords: družinsko okolje; intelektualne sposobnosti; pedagoška psihologija; razvojna psihologija; učenci; učna uspešnost; začetni pouk